2016
DOI: 10.1590/s0080-623420160000400014
|View full text |Cite
|
Sign up to set email alerts
|

Nurses in post-operative heart surgery: professional competencies and organization strategies

Abstract: Objective:To analyze nurses' competencies with regard to their work in post-operative heart surgery and the strategies implemented to mobilize these competencies. Method: This was an exploratory study with a qualitative approach and a methodological design of collective case study. It was carried out in three post-operative heart surgery units, consisting of 18 nurses. Direct observation and semi-structured interviews were employed to collect data. Data were construed through thematic analysis. Results: nine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 17 publications
1
15
0
22
Order By: Relevance
“…In this study, professionals were followed only for a part-time period, either by the nurse responsible for the work shift or other members of the Nursing team. 1 Another issue that emerged from the nurses' discourse in this study refers to the new employee's previous experience. Opinions differed on the preference for training employees with and without prior experience, as well as whether professionals with experience were from or were outside the institution.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, professionals were followed only for a part-time period, either by the nurse responsible for the work shift or other members of the Nursing team. 1 Another issue that emerged from the nurses' discourse in this study refers to the new employee's previous experience. Opinions differed on the preference for training employees with and without prior experience, as well as whether professionals with experience were from or were outside the institution.…”
Section: Discussionmentioning
confidence: 97%
“…Nursing professionals are required by the current labor market to have a series of skills and, to keep up with these demands, health institutions need to invest more and more in education so that the Nursing team can develop. 1 An essential educational tool can be considered in this context: the Admissions Training (AT) of new employees. This structured and systematic training process enables new employees to acquire and develop skills and certain competencies required by the service through practical activities and continuous supervision.…”
mentioning
confidence: 99%
“…Contudo, foi possível evidenciar, nos resultados deste estudo, que apenas 4 (8,5%) enfermeiros tinham experiência em cuidados no pós-operatório de cirurgia cardíaca, corroborando outros estudos em que os profissionais atuantes no cuidado de pacientes críticos apresentam formação profissional recente, sem experiência ou em busca de aperfeiçoamento teórico. Todavia, são pontos necessários para atuar nessa área complexa, a qual exige o desenvolvimento de habilidades 17,18 .…”
Section: Discussionunclassified
“…Sadeghi (2010) showed that 73% of nurses in Bojnoord were female [9]. In addition, Taghavi (2006) reported that 90% of nurses in Tehran City were female [11]. In general, findings revealed that the majority of nurses employed in hospitals are female.…”
Section: Discussionmentioning
confidence: 99%